(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
This study explores the pedagogical and psychological dimensions involved in shaping creative competence among music educators. It examines how creativity, as a vital teaching skill, can be cultivated through structured pedagogical approaches and supportive psychological environments. The research highlights the importance of reflective practice, emotional resilience, and institutional support in fostering innovation and adaptability in music teaching. By integrating theoretical perspectives and practical strategies, the study underscores the necessity of creativity in empowering teachers to design learner-centered, expressive, and culturally responsive music education. The findings suggest that the intersection of pedagogy and psychology is crucial for sustaining long-term professional growth and artistic development in educators.